METHODICAL GUIDE FOR DEVELOPING PATRIOTISM VIRTUES IN STUDENTS DURING THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2025)
The article discusses the methodology of developing the virtues of patriotism in students during the learning process. Information about how this methodology is implemented to enhance students' understanding of patriotism is provided. This methodology is designed to educate students about their country, nationality, and homeland, and help them strengthen their understanding of the topic through practical activities.